Improvement in joint efficiency with high productivity and narrow weld formation in friction stir welding. (April 2022) - Khan, Noor Zaman; Siddiquee, Arshad Noor; Khan, Zahid A; Badruddin, Irfan Anjum; Kamangar, Sarfaraz; Maqbool, Annayath
High productivity, excellent joint strength and small weld bead make friction stir welding an emerging joining technique to join difficult to weld dissimilar aluminum alloys. Effect of rotational speed, traverse speed and shoulder diameter on the joint strength and elongation of the friction stir welded dissimilar aluminum alloys (AA7475-AA2219) is investigated. In addition, parameters are optimized to obtain joint with narrow weld bead and high joint efficiency using the entropy-weighted technique for order of preference by similarity to ideal solution method. Nine experiments are performed as per the L9 orthogonal array and mechanical properties of the welded joints are measured. Results of the study reveal that optimum values of ultimate tensile strength and percentage elongation are obtained at a rotational speed of 710 rev/min, welding speed of 250 mm/min and shoulder diameter of 10 mm resulting in good joint strength, high productivity and narrow weld bead. From the selected process parameter range, tool shoulder diameter is found to be the most significant parameter. The findings of the present study are discussed in light of the friction stir welding process mechanism, available literature, mechanical testing, microstructure and fractography.